CECHY I EFEKTY RESTRUKTURYZACJI BIPOLARNEGO ROLNICTWA POLSKIEGO W WARUNKACH TRANSFORMACJI SYSTEMOWEJ - Kociszewski, Jerzy (Wydział Prawa i Administracji UAM, 1999)
The agriculture of ZZiP (North and West Territories of Poland) undergoes double redevelopment. The first one, 1945 - 1958, is connected with settlement and farm implements after the war and consists in the experiment of basing agriculture on the socialized property; it was continued to 1989. The second one is being performed at present and its content is the privatization of public properties and shaping, once again, new agrarian structure based on family farms. Considering the results of the socialization process it seems indispensable to adopt the State control (in the period of transition) over the rebuilding of agriculture and accumulation - for the benefit of its development in order to consolidate its economical and national identity through a system of preferences and allowances.
DISTINCTIVE FEATURES AND EFFECTS OF RESTRUCTURATION OF THE BI-POLAR POLISH AGRICULTURE UNDER RECENT SYSTEM TRANSFORMATION